2023
DOI: 10.1109/jsen.2023.3238164
|View full text |Cite
|
Sign up to set email alerts
|

Improving Detection Efficiency of Silicon Carbide Neutron Detector Using Double Trench

Abstract: In this article, we propose a double-trenchtype silicon carbide (SiC) neutron detector and model it using the concept of a unit cell on the GEANT4 platform. When the low-level discriminator (LLD) value was fixed at 300 keV, the structural parameters of this double-trench-type SiC neutron detector were optimized to maximize the intrinsic detection efficiency. Compared with the single trench type, the doubletrench-type SiC neutron detector can significantly improve the neutron intrinsic detection efficiency with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…A dual-energy detector was simulated, using Geant4 (version 10.07.p03) [10], to validate the model of the X-ray security scanner. The 128-pixel crystals were implemented using the G4Replica class [11,12]. This allowed us to differentiate the counts for each pixel.…”
Section: Jinst 19 C01050mentioning
confidence: 99%
“…A dual-energy detector was simulated, using Geant4 (version 10.07.p03) [10], to validate the model of the X-ray security scanner. The 128-pixel crystals were implemented using the G4Replica class [11,12]. This allowed us to differentiate the counts for each pixel.…”
Section: Jinst 19 C01050mentioning
confidence: 99%
“…In the case of 3 He, its scarcity makes it unsuitable as a commonly used neutron conversion material. It's found that 10 B is a preferred choice of conversion materials since it has a thermal neutron absorption cross-section of 3840 barns for neutrons with an energy of 0.025 eV which is about four times higher than that of 6 Li [7,8]. The primary reaction between neutrons and 10 B is the 10 B(n,𝛼) 7 Li reaction, as shown in equation below.…”
Section: Introductionmentioning
confidence: 99%